Different gut microbiota in U.S. formula-fed infants consuming a meat vs. dairy-based complementary foods: A randomized controlled trial - Tang, Minghua; Ma, Cheng; Weinheimer-Haus, Eileen M.; Robertson, Charles E.; Kofonow, Jennifer M.; Berman, Lillian M.; Waljee, Akbar; Zhu, Ji; Frank, Daniel N.; Krebs, Nancy F. (Frontiers in Nutrition, 2023)
Objective: This project aimed to evaluate the impact of meat- vs. dairy-based complementary foods on gut microbiota and whether it relates to growth. Design: Full-term, formula-fed infants were recruited from the metro Denver area (Colorado, US) and randomized to a meat- or dairy-based complementary diet from 5 to 12 months of age. Infant’s length and weight were measured, and stool samples were collected at 5, 10, and 12 months for 16S rRNA gene sequencing and short-chain fatty acids quantification. Results: 64 infants completed the dietary intervention (n=32/group). Weight-for-age Z (WAZ) scores increased in both groups and length-for-age Z scores (LAZ) increased in the meat group only, which led to a significant group-by-time interaction (P=0.02) of weight-for-length Z (WLZ) score. Microbiota composition (Beta-diversity) differed between groups at 12 months (weighted PERMANOVA P=0.01) and had a group-by-time interaction of P=0.09. Microbial community richness (Chao1) increased in the meat group only. Genus Akkermansia had a significant group-by-time interaction and increased in the meat group and decreased in the dairy group. A significant fold change of butyric acid from 5 to 12 months was found in the meat group (+1.75, P=0.011) but not in the dairy group. Regression analysis showed that Chao1 had a negative association with WLZ and WAZ. Several genera also had significant associations with all growth Z scores. Conclusion: Complementary feeding not only impacts infant growth but also affects gut microbiota maturation. Complementary food choices can affect both the gut microbiota diversity and structures and these changes in gut microbiota are associated with infant growth.